The Dialectics of Communicative and Immanent Critique - Johan Fornäs (tripleC: Communication, Capitalism & Critique)
In cultural studies and cultural research, the importance of being critical is often stressed, but it is more rare to scrutinise how such critique is and can be performed. This text discusses different modes of critique, in three main steps. First, a brief review of the history and signifying layers of the concept of critique itself leads up to a late modern communicative concept of critique, linked to the contested relation between critique and tradition, and based on how Paul Ricoeur has interpreted ideology critique and the hermeneutics of suspicion. This communicative mode is contrasted to critical approaches that strive to radically dissociate themselves from others. Second, it is argued that the most powerful sources of critique are to be sought in the inner contradictions of the targeted spheres of social reality rather than applied from the outside. Such immanent – as opposed to transcendent – critique, has been formulated and exercised by Karl Marx, Theodor W. Adorno and Walter Benjamin, among others. The third section sums up the spiral moves of cultural studies as informed by critical hermeneutics: dialectical critique based on communicative and immanent critique must be on the move, never frozen, and may temporarily and locally explore radical and transcendent modes of critique, in ways that have been discussed by Donna Haraway.